PENGARUH PERSEPSI KARYAWAN TENTANG KEADILAN KOMPENSASI TERHADAP KEPUASAN KERJA DI PERUSAHAAN X - Wahyudhi Sutrisno (Teknoin, 2015)
This research aims to know whether employees perception to compensation justice which is accepted affecting the level of employee’s job satisfaction. Research data obtained from primary data and secondary data. Primary data obtained by giving questionnaire to respondent. Secondary data consist of history of the company, company’s profile, organization chart, total of employees, and applied compensation system. Data analysis using the analysis of linear regression and correlation analysis. result of this research shows that there is significantly influence between employees perception to compensation justice with job satisfaction. And there is closer relationship between perception variable about justice of compensation system with job satisfaction.